Constantine - Shuler-Donner, Lauren; Lawrence, Francis; Tyler, Brian (Warner Home Video; distributed in the Philippines by Warner Home Video (Philippines), 2005)
Supernatural detective John Constantine and policewoman Angela Dodson travel to the world of demons and angels.